Sports injuries and their risk factors in adolescents who practice swimming - Vanderlei, Franciele Marques; Rossi, Renata Claudino; Vanderlei, Luiz Carlos Marques [UNESP]; Júnior, Jayme Netto [UNESP]; Pastre, Carlos Marcelo [UNESP] (My University, 2014)
Introduction: swimming is a popular sport among adolescents; however, your practice can lead to injuries. Objectives: to characterize the sport injuries and associate them with risk factors in teenage swimmers from different levels of competitiveness. Methods: 251 swimmers were interviewed, it an average age of 12.43±2.10, both sexes, recruited randomly and they were classified into three competitive levels: initiation, development, and training category. It was used the morbidity survey adapted to the characteristics of swimming as collection instrument containing personal and training of volunteers data, as age, anthropometric variables and training variables and information relating to injuries sustained during a period of 12 months. All findings were described at the 5% significance level. Results: It was verified that there is an association between the presence and absence of injury with the variable height and variable time. The causal mechanism most common was the non-contact mechanism for the categories of initiation and training. The most affected anatomical site was the lower limb and upper limb for all competitive levels. The mild severity, the training time and the absence of recurrence predominated. The asymptomatic return was more frequent for initiation, whereas the symptomatic return prevailed in the training category. Conclusion: the injury rate in teenage swimmers was low. The variables height and training time were associated with the occurrence of injuries. The characteristics of the injuries depended on the competitive level of the swimmers.
Keywords: Athletic injuries; Risk factors and morbidity surveys; Swimming